"How do Pilates Trained Physiotherapists utilize and value Pilates Exercise for MSK conditions? A Qualitative Study". (6th April 2020) - Cuddy, Peter; Gaskell, Lynne
Abstract: Background: Pilates is a popular exercise therapy approach offering numerous benefits, including muscular strength, flexibility, control, and core stability. Pilates has been widely utilized in the prevention and rehabilitation of a variety of musculoskeletal disorders. Objectives: The aim of this study was to explore the experiences and opinions of Pilates trained NHS and private practice physiotherapists in the UK, regarding the perceived benefits, risks, delivery and rationale for this exercise method. Methods: This qualitative study used a self‐designed electronic survey to retrieve the views of 30 physiotherapists, who had undertaken formal Pilates Instruction training, recruited by a purposive and snowball sampling method. Questions were either multiple choice or open‐ended, examined via thematic analysis. Results: Physiotherapists identified the most important benefits of Pilates as reduction in fear‐avoidance, improving bodily awareness and increasing muscular strength. Exercises that promote general movement were highlighted as being particularly useful, with a majority recommending daily practice for optimum benefit. Participants recognized lack of core strength as a key indicator, whereas others criticized excessive focus on this principle. Conclusions: Physiotherapists identified a range of inter‐linked benefits and recognized that Pilates is hugely modifiable. Individualizing exercises can further encourage participation and negate the restriction of some health conditions. NHS and Private Practice Therapists utilize Pilates in a similar way, although rationales for its use may differ, as the justification for Pilates exercise may be evolving. Pilates appears a valuable methodology in the NHS, which can help patients engage with activity.